Optimizing blueberry (Vaccinium corymbosum L.) yield with strategic foliar application of putrescin and spermidine at key growth stages through biochemical and anatomical changes - Karami, Amir Ali; Abdossi, Vahid; Ghanbari Jahromi, Marzieh; Aboutalebi Jahromi, Abdolhosain (Frontiers in Plant Science, 2025)
Foliar spraying of polyamines, such as putrescine (Put) and spermidine (Spd), has been shown to improve plant and fruit yield. However, the optimal time for spraying these polyamines is still uncertain. The present study was conducted to evaluate plant growth, stomatal parameters, and biochemical attributes of blueberry (Vaccinium corymbosum L.) under Put and Spd application at various spraying times. Plants received spray treatments with doses of 0.5 and 1 mM of Put and Spd during bloom, fruit development, and ripening stages. According to the findings, both Put and Spd enhanced fruit and plant yield, although Put had a greater effect. The best timing to apply foliar spraying was observed during the fruit development stage. In plants sprayed at the fruit development stage, Put at 1 mM led to increased plant height (11%), SPAD value (17%), fruit yield (80%), fruit firmness (34%), anthocyanin (31%), total phenolic content (TPC, 14%), total flavonoid content (TFC, 35%), stomatal length (45%), stomatal width (40%), nitrogen (N, 43%), phosphorous (P, 21%), and potassium (K, 18%), but decreased antioxidant capacity (IC50, 36%) and stomatal density (19%) relative to the control. In response to the management for bloom, fruit development, and ripening stages, fruit yield in plants sprayed with Put at 1 mM increased by 55, 80, and 64%, respectively. Heat map analysis revealed the maximum variability among traits associated with fruit yield under the treatments. The research suggests that strategic foliar application of Put and Spd at specific growth stages can enhance blueberry yield and quality, with the fruit development stage showing promising results.